Characterization of the microtranscriptome of macrophages infected with virulent, attenuated and saprophyte strains of Leptospira spp. - Leandro Encarnação Garcia; Erivelto Corrêa de Araújo Junior; Larissa Martins Melo; Jaqueline Poleto Bragato; Juliana Regina Peiró; Valéria Marçal Félix de Lima; Márcia Marinho; Daniel Robert Arnold; Flavia Lombardi Lopes (Public Library of Science (PLoS), 2018)
Leptospirosis is a bacterial zoonosis, caused by Leptospira spp., that leads to significant morbidity and mortality worldwide. Despite considerable advances, much is yet to be discovered about disease pathogenicity. The influence of epigenetic mechanisms, particularly RNA-mediated post-transcriptional regulation of host immune response has been described following a variety of bacterial infections. The current study examined the microtranscriptome of macrophages J774A.1 following an 8h infection with virulent, attenuated and saprophyte strains of Leptospira. Microarray analysis revealed that 29 miRNAs were misregulated following leptospiral infection compared to control macrophages in a strain and virulence-specific manner. Pathway analysis for targets of these differentially expressed miRNAs suggests that several processes involved in immune response could be regulated by miRNAs. Our data provides the first evidence that host miRNAs are regulated by Leptospira infection in macrophages. A number of the identified miRNA targets participate in key immune response processes. We suggest that post-transcriptional regulation by miRNAs may play a role in host response to infection in leptospirosis.